Clinical risk factors for cutaneous squamous cell carcinoma in patients with actinic keratosis or cutaneous squamous cell carcinoma in situ: A retrospective double-cohort study - Kaijala, Olli (My University, 2023)
Actinic keratoses (AK) and cutaneous squamous cell carcinoma in situ (cSCCIS) are precancerous forms of squamous cell carcinoma (cSCC). This single center study, sought to investigate clinical risk factors for cSCC progression in AK and cSCCIS patients during a 5-year observation period. Two separate, retrospective cohort comparisons were generated. First AKs without cSCC progression (n=82) and with cSCC progression (n=37) and cSCCIS without cSCC progression (n=85) and second with cSCC progression (n=14). Higher risk for cSCC development in AK patients was observed for male gender, age, and immunosuppressed status. Location in the head area and lower dysplasia grade of the initial AK lesion was associated with lower cSCC risk. This study offers additional evidence for previously established risk factors and raises questions on the value of AK lesion characteristics in designing follow-up protocols.